2008
DOI: 10.1179/174329408x315454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of montmorillonite on properties of nanocomposite coatings

Abstract: Unmodified or chemically modified montmorillonite (MMT) dispersed in water was added into the reaction mixture forming hybrid organic-inorganic (O-I) nanocomposite coating. Two basic systems made from functionalised trialkoxysilane and oligomeric diamine v. functionalised dialkoxysilane and triamine were prepared and compared. End properties depend not only on the concentration and kind of MMT used but also on the inner constitution of the O-I matrix. Already 1 wt-% of unmodified MMT influences considerably su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Even the small amounts (0.5 wt%) of the different nanoadditives studied in this work led to distinct differences in surface topography and roughness of the coating films prepared. In our previous work 15, [17][18][19] we have already shown that the relief of coatings without any additive or of such filled with varying contents of colloidal silica is very regular even in sub-micrometer scale. If any layered nanoadditive (LN) is used as an admixture, the relief becomes more rugged and the individual layers are typically clustered to self-assembled formations of different size and shape, depending on the type of LN used.…”
Section: Surface Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations
“…Even the small amounts (0.5 wt%) of the different nanoadditives studied in this work led to distinct differences in surface topography and roughness of the coating films prepared. In our previous work 15, [17][18][19] we have already shown that the relief of coatings without any additive or of such filled with varying contents of colloidal silica is very regular even in sub-micrometer scale. If any layered nanoadditive (LN) is used as an admixture, the relief becomes more rugged and the individual layers are typically clustered to self-assembled formations of different size and shape, depending on the type of LN used.…”
Section: Surface Characteristicsmentioning
confidence: 96%
“…These effects were caused by incorporation of nanofillers, namely of 5-20 wt% SiO 2 15,17-19 or of 1-5 wt% of montmorillonites MNa or K30. [18][19][20] In the present work, the influence of silicate nanofillers at a much lower concentration, 0.5 wt%, was studied, with special interest on two newly tested montmorillonite nanofillers, bentonite for water systems (BW) and laponite (LX). The 13 C CP/MAS NMR spectra confirm the expected chemical composition and make possible to evaluate the conversion of epoxy-amine addition (step 2 of matrix synthesis).…”
Section: Solid-state Nmr ( 13 C and 29 Si Cp/mas) Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…As nanofiller, colloidal silica (in concentrations from 0.5 to 20 wt% [24][25][26][27] ) and unmodified and several chemically modified montmorillonites at concentrations ranging from 0.5 to 5 wt% [26][27][28] were used. The previous study by the authors 27 was aimed at studying the effect of small amounts of inorganic nanofillers on the nanocomposite properties.…”
Section: Introductionmentioning
confidence: 99%